1994
DOI: 10.1002/1097-0142(19940315)73:6<1673::aid-cncr2820730620>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating lobular carcinoma. Is it different from infiltrating duct carcinoma?

Abstract: Background. Infiltrating lobular carcinomas (ILC) represent approximately 10% of all breast cancers. The literature is mixed regarding their prognosis when compared with infiltrating duct carcinomas (IDC). There are few data regarding the treatment of ILC with radiation therapy. Methods. The clinical, pathologic, laboratory, and survival data of 161 patients with ILC were compared with the data of 1138 patients with IDC. Results. ILCs were larger, more difficult to excise completely, and more difficult to diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
108
1
9

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(129 citation statements)
references
References 19 publications
11
108
1
9
Order By: Relevance
“…In line with the present findings, Dixon et al (1985) found in their series of 105 patients that those with ILC have better outcome than those with IDC. A similar conclusion was reached by Du Toit et al (1991) and Silverstein et al (1994) in their studies consisting of 171 and 161 patients respectively. DiCostanzo et al (1990) compared survival of 230 patients with ILC with stagematched patients with IDC.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with the present findings, Dixon et al (1985) found in their series of 105 patients that those with ILC have better outcome than those with IDC. A similar conclusion was reached by Du Toit et al (1991) and Silverstein et al (1994) in their studies consisting of 171 and 161 patients respectively. DiCostanzo et al (1990) compared survival of 230 patients with ILC with stagematched patients with IDC.…”
Section: Discussionsupporting
confidence: 82%
“…ILCs have also. been found to be associated with a low histological grade by others (Silverstein et al, 1994;Sastre-Garau et al, 1996), but reports on the frequency of axillary nodal involvement are contradictory (Silverstein et al, 1994;Sastre-Garau et al, 1996). ILCs have been reported to express more often oestrogen and progesterone receptors (Helin et al, 1989;Sastre-Garau et al, 1996) and less often erbB-2 and p53 oncogenes (Toikkanen et al, 1992;Rosen et al, 1995) than IDCs, and their bcl-2 expression has been reported to be stronger than that of IDCs (Joensuu et al, 1994); these findings also suggest that ILC is biologically less aggressive than IDC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology categories special type and comedocarcinoma were associated with lower RERs of death than infiltracting ductal carcinoma (Table 5). The special type category includes, tubular, mucinous and papillary histotypes, which were reported to have good prognoses in a previous population-based study (Li et al, 2003), and in other studies (Cooper et al, 1978;Fisher et al, 1980;Wargotz and Silverberg, 1988;Ellis et al, 1992;Silverstein et al, 1994;Pedersen et al, 1995;Reinfuss et al, 1995;Toikkanen et al, 1997;Diab et al, 1999). Comedocarcinoma also had a relatively good prognosis in a previous study (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 77%
“…Further, the differences in stage, tumour size, and lymph node status observed here may reflect differences in the utility of screening approaches to detect different histologic types of cancer. For example, it is well known that lobular tumours are more difficult to detect with mammography compared to ductal tumours, and this is thought to be primarily due to the fact that lobular tumours tend to grow as linear strands or sheets of cancer cells rather than as more discrete masses, explaining why they are more likely to be diagnosed at a more advanced stage (Davis et al, 1979;Dixon et al, 1982;Silverstein et al, 1994;Yeatman et al, 1995). Thus, currently, available breast cancer screening tools appear to be relatively less or relatively more effective in detecting different histopathologic types of breast cancer.…”
Section: Discussionmentioning
confidence: 99%